Dampak Penggunaan Varietas Unggul terhadap Distribusi Pendapatan Petani Jagung di Kalimantan Barat - Kusrini, Novira; Irham, Irham; D., Dwidjono H.; Jamhari, Jamhari (Universitas Brawijaya, Indonesia, 2009)
The objectives of the study are (1) to analyze the household's income structure of corn farmers based on variety types and land holdings and (2) to see the relation between income distribution and land holding and types of variety. Data analyzed in the study were collected from two main corn-producing districts during the planting seasons of 2007/2008. Results of the study show that share of income from farm business to the total households' income is relatively high, i.e., shares of income from corn farming based on variety type varied from 44 to 87 percent in Sinar Tebudak and 49 to 87 percent in Pangmilang. Distribution of corn farming income for all types of variety is more balanced than that of total households' income due to variation in non-farm income. The study also indicates that there is a positive correlation in all variety types between total households' income and land holding. The use of superior variety could improve distribution of corn farming income and distribution of households' income. Implications of the study are (1) enhancing non-farm employment in rural areas is essential to improve households' income; (2) implementing land reform is one of the instruments to create a better distribution of land holding and income distribution in rural areas; and (3) improving supporting inputs and facilities like water irrigation, fertilizer, pesticide, credit and agricultural extension service for the corn farmers are essential in order to improve income distribution in the study area.